Exploring the myth of “Orpheus and Eurydice” in the classroom with the use of Inquiry Drama Method - Papadopoulos, Simos; Papakosta, Alexia (Epistēmēs Metron Logos, 2023)
This article focuses on the dramatic exploration of the ancient Greek myth of “Orpheus and Eurydice”. Our aim is to approach issues and concepts concerning nature, man and life, with the use of appropriate drama techniques based on the Inquiry Drama method which, through critical thinking and playful, improvised and organized stage exploration, pursues self-consciousness along with the change of attitudes and behaviors for the confrontation of timeless everyday life issues.